The Urgency of Interactive Learning Media in Improving Students’ Physics Learning Outcomes - Andani, Sri Rahayu; Sari, Silvi Yulia; Akmam, Akmam; Sundari, Putri Dwi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Using media in the classroom can improve comprehension, convey trustworthy and engaging facts, facilitate data interpretation, and condense material for students. The purpose of this study is to evaluate how urgently or significantly interactive learning materials can enhance student learning outcomes. The research methodology employed is a survey of the literature, which involves reading several articles from both domestic and foreign publications about the application of interactive learning media to enhance learning outcomes. The study's findings demonstrate how crucial it is to employ interactive learning resources to raise student learning objectives.